Rapid determination of lignosulfonate depolymerization products by advanced polymer chromatography. Issue 13 (7th June 2019) - Qian, Chen; Fang, Hongxia; Cui, Peng; Cai, Fang; Gao, Xinyu; He, Hualong; Hu, Xiaopo
Abstract: Depolymerized lignin products are very complex mixtures. Based on a depolymerization solution of commercially available sodium lignosulfonate under mild conditions, a fast and efficient method for the separation and direct characterization of the degree and efficiency of the acid‐catalyzed depolymerization of lignin was developed in this study. Using an ultraviolet detector, the depolymerized lignosulfonate products were well separated and characterized according to the relative molar mass distribution on an advanced polymer chromatographic system with three ethylene‐bridged hybrid columns having small pore sizes (45 Å) in series and tetrahydrofuran as the mobile phase. The developed advanced polymer chromatography method enabled the detection of low‐molecular‐weight lignin degradation products ( M n = 260–1100 Da) with high peak resolutions in less than 7.2 min. Furthermore, preliminary advanced polymer chromatography studies to determine the influence of reaction temperature on the depolymerized products indicated that the depolymerized aromatics fell in several molecular weight ranges with an extremely low dispersity. This new approach can be used for the rapid analysis of lignin depolymerization products.